2008
DOI: 10.1007/bf03175530
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of nematicidal strainSyncephalastrum racemosum

Abstract: Nematicidal activity using a pure culture of Syncephalastrum racemosum was studied. The results showed that the metabolites of S. racemosum have pretty high nematicidal activity. The nematicidal principles were soluble in water and had high thermal stability. The major acid metabolites extracted from cultures of S. racemosum identified from HPLC were oxalic acid dihydrate and tartaric acid. Soil application with culture filtrate of S. racemosum significantly (P < 0.05) reduced nematode population densities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…In addition, Sun et al (1999) reported that all the isolates of S. racemosum obtained from soil were effective at colonizing eggs of M. incognita. However, the same level of efficacy was not observed at higher densities of the nematode (Sun et al, 2008). On susceptible cucumber plants, less effect of this fungus was observed at higher M. incognita densities compared to lower densities.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…In addition, Sun et al (1999) reported that all the isolates of S. racemosum obtained from soil were effective at colonizing eggs of M. incognita. However, the same level of efficacy was not observed at higher densities of the nematode (Sun et al, 2008). On susceptible cucumber plants, less effect of this fungus was observed at higher M. incognita densities compared to lower densities.…”
Section: Discussioncontrasting
confidence: 58%
“…Spore suspension of S. racemosum was inoculated on potato sucrose (PS) liquid medium to a final concentration of 10 7 spores ml À1 (Sun et al, 2008). As described by Huang et al (2014), fermentations were performed in a 30 L fermenter containing the PS liquid medium at 27°C for 42 h, and the cultured filtrate and mycelium were used for next experiment after filtration.…”
Section: Culturing and Maintenance Of Biocontrol Microorganismsmentioning
confidence: 99%
See 2 more Smart Citations
“…They cause serious losses both in the field and post-harvest, and some may produce mycotoxins (Strange and Scott 2005). Various artificial chemical fungicides have been successfully developed and applied to fields to control fungal diseases (Sun et al 2008). However, because of their huge populations and high frequency of mutation, pathogenic fungi may easily acquire resistance to frequently used fungicides.…”
Section: Introductionmentioning
confidence: 99%